Parenting style and students’ happiness in China - Satrio, Prakrisno; Wu, Lin; Cheng, Chen; Qian, Kuang; Ho, Yi Ming; Prihadi, Kususanto Ditto (Journal of Education and Learning (EduLearn), 2024)
This study examined the dynamic between perceived authoritarian parenting style (PAPS), and subjective wellbeing (SWB) among purposively recruited 423 college students in China. Expectancy value beliefs (EVB), fear of failure (FOF), and competitiveness were taken as mediators. The data were analyzed using Bootstrap method of 5000 sample and 95% confidence interval. The results revealed a significant negative total effect of PAPS on SWB. Additionally, two indirect paths were found to be significant: the mediation of FOF (Path 2) and the serial mediation of FOF and competitiveness (Path 6). These findings suggest that the perception of authoritarian parenting style is a negative predictor of students' happiness, and that FOF and competitiveness played important mediating roles in this relationship. These findings have important implications for educators, parents, and policymakers who aim to promote positive academic and personal outcomes for college students. The results suggest the need for interventions that address the negative impact of PAPS on students' wellbeing, and the importance of fostering positive beliefs about the value of education and academic achievement, as well as reducing FOF and promoting healthy competition.